Five Years Follow-Up of Acrysof Cachet® Angle-Supported Phakic Intraocular Lens Implantation for Myopia Correction. (26th March 2022) - Musayeva, Aytan; Riedl, Jana C.; Gericke, Adrian; Vossmerbaeumer, Urs
Abstract : Purpose . The Acrysof Cachet® angle-supported phakic intraocular lens (pIOL) (Alcon Laboratories, Inc., Fort Worth, TX) is designed to correct high refractive errors in human eyes. The aim of this study was to evaluate the outcome of AcrySof Cachet® angle-supported pIOL implantation with particular regard to efficacy and safety of the implant over a 60-month follow-up period. Design . Retrospective consecutive clinical case study. Methods . Prior to pIOL implantation, patients had a complete ophthalmologic examination including objective and subjective refraction, uncorrected visual acuity (UCVA) and corrected distance visual acuity (CDVA), endothelial cells density (ECD), slit lamp photography, optical coherence tomography (OCT), Scheimpflug digital videokeratoscopy, optical biometry, slit lamp examination, intraocular pressure (IOP) measurement, and pupillometry. Postoperatively, patients received yearly a complete eye examination. Results . Thirty-one eyes of 16 patients were included in this study. The mean age was 36.2 ± 8.1 years. UCVA (logMAR) improved from 1.33 ± 0.20 before surgery to 0.08 ± 0.14 one year after surgery and was 0.20 ± 0.20 five years after surgery. CDVA (logMAR) improved from 0.10 ± 0.10 before surgery to 0.05 ± 0.13 one year after surgery and was 0.04 ± 0.14 five years postoperatively. The mean percentage of endothelial cells loss (ECL) was 11.51% over the first year and 15.95% five years after surgery. There were no intraoperative complications in any of the eyes. Conclusions . Our results up to five years after implantation of the AcrySof Cachet® angle-supported pIOL demonstrated very good outcomes in all above shown measurements, including CDVA, UCVA, and ECD. However, since major endothelial cell loss may occur in some patients with this type of pIOL, regular follow-up visits are required.